DIALEKTIKA AGAMA MISSI: STUDI INTERAKSI SOSIAL PEMELUK AGAMA ISLAM, KATOLIK, DAN BUDDHA DI MARGOREJO KABUPATEN PESAWARAN PROVINSI LAMPUNG - Idrus Ruslan (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
Human are social beings that cannot avoid the social interaction because they establish some communication. Some missionary religions are found in Margorejo (Islam, Christianity, and Buddhism). Even though the religions are different but the social interaction is very good. The result of this qualitative research shows that the social interaction among religious groups is associative model that emphasizes on social cooperation and religious tolerance. Besides it is found a particular media called “ Tri Budaya” used to build social interaction. Tri Budaya is the art like ludruk (typical Javanese art) that is played by many religious communities in Margorejo. Some factors that influence social interaction of missionary religions in Margorejo are district condition, imitation and sympathy, ethnic and language equality, and support from religions figures and rural district’s leaders.